Effects of thyroid hormones modify the association between pre-pregnancy obesity and GDM: evidence from a mediation analysis - Alifu, Xialidan; Chen, Zexin; Zhuang, Yan; Chi, Peihan; Cheng, Haoyue; Qiu, Yiwen; Huang, Ye; Zhang, Libi; Ainiwan, Diliyaer; Si, Shuting; Peng, Zhicheng; Zhou, Haibo; et al. (Frontiers in Endocrinology, 2024)
Objective Conflicting associations have been noted between thyroid function and gestational diabetes mellitus (GDM), with indications that pre-pregnancy BMI might influence these relationships. This study aims to examine the effect of thyroid hormone indices and their mediation role on the risk of GDM. Methods Pregnant women in our study were recruited from the Zhoushan Pregnant Women Cohort, Zhejiang Province, China. Participants who had their first prenatal follow-up and measured thyroid biomarkers in the first trimester, and oral glucose tolerance test (OGTT) records in the second trimester were eligible for inclusion in this study. The data were extracted from the Electronic Medical Record System database, at Zhoushan Maternal and Child Care Hospital. Maternal information about sociodemographic and health-related characteristics was extracted from the dataset. A unique personal identification number was provided to link both datasets. Multivariate logistic regression models were applied to investigate the correlations between thyroid hormone indices with GDM. The interaction effects of first-trimester thyroid hormone indices with pre-pregnancy BMI on GDM risk using a generalized linear regression model. Furthermore, the mediation analysis was used to explore the potential mediating effects of thyroid hormone indices on the relationship between pre-pregnancy BMI and GDM. Results Overall, 5895 pregnant women were included in this study. The first-trimester FT4, thyroid feedback quantile-based index (TFQI), thyrotropin index (TSHI) and thyrotroph thyroxine resistance index (TT4RI) levels were negatively associated with fasting blood glucose (FBG) and postprandial blood glucose (PBG2H) in the second trimester (all P<0.05); FT3 and the FT3-to-FT4 ratio levels were positively associated with PBG1H and PBG2H in the second trimester (all P<0.05). Moreover, there were significant correlations between the highest quartile FT4, FT3, FT3-to-FT4 ratio, TSHI, and TFQI with GDM (all P < 0.05). The mediating effect of thyroid hormone parameters was 24.9% on the association between pre-pregnancy BMI and GDM. Conclusions In conclusion, the low FT4, high FT3-to-FT4 ratio, and low TFQI in the first trimester significantly increase the risk of GDM and should be given more attention. Furthermore, increased pre-pregnancy BMI might partially increase the risk of GDM by influencing the body’s thyroid function.